(untitled) (Journal of the College of Basic Education, 2026)
Ambiguity is an important rhetorical term that has not received its due attention in research and investigation. It has been sufficient to focus on the negative aspect of ambiguity, which is obscurity and lack of clarity. Research has come to reveal the positive aspect of ambiguity, which is expanding and diversifying the meaning in a way that serves the reader - any reader - to understand the details of the speech and the scene that is to be depicted. The Holy Qur’an contains ambiguity in its positive aspect and it has an active presence in the integration of scenes and the openness of their meaning, especially when dealing with psychological states and mental perceptions that are difficult to express. Thus, the positive ambiguity comes to make the reader the one who completes the scene and draws its image in his mind according to what he has of diverse historical, cultural and environmental references.